KHUSNUDZON DAN PSYCHOLOGICAL WELL BEING PADA ORANG DENGAN HIV/AIDS - Qurotul Uyun; Irman Nuryadin Siddik (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2017)
The aims of this research is determine the relation between khusnudzon and psychological well being in people living with HIV / AIDS. The hypothesis in this research is there is positive relation between khusnudzon psychological well being in people living with HIV / AIDS. To test the hypothesis of the research, researchers collecting data using a scale of psychological well being adapted from a Ryff’s scale (1989) and adapted khusnudzon scale of Dewi’s scale (2015) is based on the theory from Rusydi (2012). The scale distributed to 55 people living with HIV/ AIDS who are the members of the VP foundation. Correlation analysis show the coefficient of r = 0.543 with significance (p) <0,01 so that hypothesis is accepted.